Profiles of Behavioral Self-Regulation and Appetitive Traits in Preschool Children: Associations With BMI and Food Parenting Practices - Francis, Lori A.; Rollins, Brandi Y.; Keller, Kathleen L.; Nix, Robert L.; Savage, Jennifer S. (Frontiers in Nutrition, 2022)
Appetitive traits that contribute to appetite self-regulation have been shown to relate to non-food-related regulation in general domains of child development. Latent profile analysis (LPA) was used to identify typologies of preschool children’s behavioral self-regulation (BSR) and appetitive traits related to appetite self-regulation (ASR), and we examined their relation with children’s BMIz and food parenting practices. Participants included 720 children and their parents (90% mothers), drawn from the baseline assessment of a childhood obesity preventive intervention. BSR measures included teacher reports of children’s inhibitory control, impulsivity and attentional focusing, as well as an observed measure of inhibitory control. ASR was assessed using parents’ reports of children’s appetitive traits related to food avoidance (e.g., satiety responsiveness, slowness in eating) and food approach (e.g., enjoyment of food, food responsiveness). Children’s body mass index z-score (BMIz) was calculated from measured height and weight. Parents’ BMI and food parenting practices were also measured. Four profiles were identified that characterized children with dysregulated behavior, higher food approach and lower food avoidance (16%), dysregulated behavior but lower food approach and higher food avoidance (33%), regulated behavior but highest food approach and lowest food avoidance (16%), and highly-regulated behavior, lowest food approach and highest food avoidance (35%). Children’s BMIz was highest in the profile consisting of children with dysregulated behavior, higher food approach and lower food avoidance. BMI was similar in the profile with children with regulated behavior but highest food approach and lowest food avoidance; children in this profile also had parents who reported the highest levels of controlling food parenting practices, and the lowest levels of parental modeling of healthy eating. Compared to all other profiles, children in the profile characterized by highly-regulated behavior, lowest food approach and highest food avoidance had the lowest BMIz and had parents who reported food parenting practices characterized by the highest levels of child control in feeding and the lowest levels of pressure to eat. These findings provide evidence of differing patterns of relations between self-regulation across behavioral and eating domains, and children’s obesity risk may vary based on these different patterns.